1994
DOI: 10.1016/0014-5793(94)01189-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the axial heme ligands of cytochrome b556 in succinate: Ubiquinone oxidoreductase from Escherichia coli

Abstract: Electron paramagnetic resonance (EPR) and near-infrared magnetic circular dichroism (MCD) have been used to identify the ligands to the cytochrome b556 component of succinate: ubiquinone oxidoreductase (succinate dehydrogenase) from Escherichia coll. The 'highly axial low spin' (HALS) EPR spectrum suggests bis(histidine) ligation of the heme with the histidines in a staggered configuration. The near-infrared MCD spectrum exhibits a low energy maximum at 1600 nm which is also clearly indicative of bis(histidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…In contrast to subunits A and B, they display generally little sequence conservation except for the pattern of hydrophobic segments (19). The so-called one-polypeptide anchors, e.g., those of B. subtilis SQR (18) and W. succinogenes QFR (32), show a common motif of five predicted transmembrane ␣-helical segments, whereas both polypeptides of two-polypeptide anchors, e.g., E. coli SdhC/D and FrdC/D, contain three predicted transmembrane segments (44). Hydrophobicity analysis of the S. acidocaldarius SdhC and SdhD subunits is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to subunits A and B, they display generally little sequence conservation except for the pattern of hydrophobic segments (19). The so-called one-polypeptide anchors, e.g., those of B. subtilis SQR (18) and W. succinogenes QFR (32), show a common motif of five predicted transmembrane ␣-helical segments, whereas both polypeptides of two-polypeptide anchors, e.g., E. coli SdhC/D and FrdC/D, contain three predicted transmembrane segments (44). Hydrophobicity analysis of the S. acidocaldarius SdhC and SdhD subunits is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hydrophobic subunits of many organisms contain one (e.g., E. coli SQR [44]) or two (e.g., B. subtilis SQR [18]) b-type cytochromes, whereas other enzymes (e.g., E. coli QFR [13]) do not contain any b-type cytochromes. The function of prosthetic heme groups, particularly in internal electron transfer, has not been determined, but they are suggested to play a structural role in stabilizing the transmembrane helices and to be important in assembly of the enzyme complex (19,43).…”
mentioning
confidence: 99%
“…The strategy for this study was in vivo complementation by a combination of sdh genes on different vectors, a method that was used successfully to investigate the assembly of E. coli FRD (33). Our recent analysis by EPR and MCD showed that the heme b 556 component of E. coli complex II is ligated to the protein by two histidine residues (38). Furthermore, His 84 in cybL and His 71 in cybS were determined to be possible heme axial ligands in cytochrome b 556 as shown using site-directed mutants.…”
Section: Discussionmentioning
confidence: 99%
“…We also have established a one-step protocol to purify complex II by chromatography using an E. coli strain that overproduces the enzyme by 10-fold due to the presence of a multicopy plasmid containing the cloned sdh operon (6). Using this preparation, bis-histidine ligation of the heme in cytochrome b 556 was demonstrated by EPR and MCD (38). However, it is not known whether cybL alone or cybL plus cybS provide coordination to the heme.…”
mentioning
confidence: 99%
“…The single heme in mammalian and E. coli SQR and the two hemes in B. subtilis SQR have bis-histidine axial ligation as demonstrated by EPR spectroscopy combined with lowtemperature near-infrared MCD spectroscopy [13][14][15]. The ligand histidine residues have been identified in the primary sequence of the B. subtilis and E. coli SQR anchor polypeptides by site directed mutagenesis analysis [12,16,17].…”
Section: The Cytoehrome B Componentmentioning
confidence: 99%